Aspek-Aspek Pelanggaran Israel Terhadap Konvensi Jenewa Dalam Konflik Israel-Palestina (Aspects of Israel's Violations of The Geneva Conventions In The Israel-Palestine Conflict) - Damareka, Muhammad Darrell; Anjani, Indira Emilia (Media Hukum Indonesia (MHI), 2025)
The Israeli–Palestinian conflict is one of the longest and most complex conflicts in the world, which is not only backgrounded by political factors, but also aspects of trust and identity. This article discusses specifically aspects of Israel’s alleged violations of the 1949 Geneva Conventions in the context of this conflict. Although Israel has ratified all parts of the Geneva Convention and its additional protocols, various reports and studies indicate the existence of serious violations of the principles of humanitarian protection regulated in the convention. The most prominent violations include the forced displacement of the Palestinian civilian population, the mass killing of civilians, as well as the detention and inhumane treatment of Palestinian children. These actions violate a number of articles in the Geneva Conventions, such as Article 49 on the prohibition of forced transfers, Article 47 on the protection of civilians, and Article 31 which provides special protection for children. Although the international world, including the United Nations and human rights agencies, has denounced these violations, enforcement of international law against Israel still faces major challenges at the political and judicial levels. This article affirms the importance of the enforcement of international humanitarian law and the protection of human rights in armed conflict, as well as the need for a real commitment on all sides to halt violations and seek peaceful solutions that are just for both sides.